2021
DOI: 10.1002/cjoc.202100226
|View full text |Cite
|
Sign up to set email alerts
|

Diversified Polyketides and Nitrogenous Compounds from the Mangrove Endophytic Fungus Penicillium steckiiSCSIO 41025

Abstract: Mangrove endophytic fungus | Penicillium steckii | Polyketides | Alkaloids | Biological activityFour new polyketide decalin derivatives, penicisteck acids A-D (1-4), and three new nitrogenous compounds (7-9), together with eight previously reported compounds, were isolated from the mangrove endophytic fungus Penicillium steckii SCSIO 41025. Their structures and absolute configurations were characterized by analysis of comprehensive spectroscopic data combined with ECD calculations and modified Marfey's method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…These results indicated that compound 13 attenuated the acute lung injury (ALI) caused by LPS-induced inflammation. Furthermore, “cytokine storm” is well characterized in ALI ( Chen et al, 2021c ). The cytokine detection in the bronchoalveolar lavage fluid (BALF) revealed that the levels of pro-inflammatory factors, such as IL-6, TNF- α , and MCP-1, in compound 13 administrated group were generally lower ( Figure 6C ) than those of the model group.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that compound 13 attenuated the acute lung injury (ALI) caused by LPS-induced inflammation. Furthermore, “cytokine storm” is well characterized in ALI ( Chen et al, 2021c ). The cytokine detection in the bronchoalveolar lavage fluid (BALF) revealed that the levels of pro-inflammatory factors, such as IL-6, TNF- α , and MCP-1, in compound 13 administrated group were generally lower ( Figure 6C ) than those of the model group.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, eight new polyketide derivatives ( 1 – 8 ) and two related known analogues ( 9 and 10 ) were identified from the endozoic fungus P. steckii AS-324, which was obtained from the fresh tissues of deep-sea Acanthogorgiidae sp. coral collected from Magellan seamount in the Western Pacific Ocean at a depth of 1458 m. Compounds 1 – 3 , with an acrylic acid side chain at C-4, have been rarely observed [ 28 ], and the double bond between C-12 and C-13 in compound 4 is a new observation. Antimicrobial activities of compounds 1 – 10 were tested, and compound 8 showed potent activity against E. coli with an MIC value of 8 μg/mL while compound 10 exhibited inhibitory activity against E. tarda with an MIC value of 16 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial effects against a panel of marine biofilm-forming bacterial strains, including methicillin-resistant Staphylococcus aureus , Pseudomonas aeruginosa , Vibrio parahemolyticus , V. alginolyticus , V. tubiashii , Microbulbifer variabilis , Marinobacterium jannaschii , V. pelagius , V. rotiferianus , and Alteromonas macleodii , were tested using our previously reported method [ 30 ]. Chloramphenicol, nalidixic acid, streptomycin, and/or ampicillin were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%